1992
DOI: 10.1071/ar9920751
|View full text |Cite
|
Sign up to set email alerts
|

Annual Medicago species in Morocco. II. Distribution in relation to soil and climate

Abstract: An ecogeographic survey was conducted in six key agricultural zones in Morocco to study the relationship between the natural distribution of medic species and soil and climatic measurements. At each of the 161 sites visited, the presence of medic species was recorded, and soil samples collected. Climatic data were obtained from published records. The influence of soil factors on the presence of medic species was more important than that of climate. With the exception of M. truncatula and M. minima, there were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…In general, greater species and ecotypic diversity is found where conditions are most favorable (Ehrman & Cocks, 1990). Bounejmate et al (1992b) were able to show that more medic species were found in M orocco at sites with near± neutral pH, high soil phosphorus status, and high clay content.…”
Section: A Ewingmentioning
confidence: 94%
“…In general, greater species and ecotypic diversity is found where conditions are most favorable (Ehrman & Cocks, 1990). Bounejmate et al (1992b) were able to show that more medic species were found in M orocco at sites with near± neutral pH, high soil phosphorus status, and high clay content.…”
Section: A Ewingmentioning
confidence: 94%
“…Au Maroc, Bounejmate ( 1992) et Bounejmate et a/. ( 1992aBounejmate et a/. ( , 1992bBounejmate et a/.…”
Section: Abstract-m Ci/iaris and M Intertexta Taxons Are Relativelunclassified
“…It also results from this that the geographical distribution of M. intertexta is limited to the North-East of Algeria, under a sub-humid and humid bioclimate, on soils low in calcium and in altitudes below 250 m in mean. (Piano eta/., 1991 ), en Espagne et Portugal (Prosperi et a/., 1989), au Maroc (Bounejmate et a/., 1992b ), en Algerie (Abdelguerfi eta/., 1988b;Adem, 1989;Abdelguerfi, 1995) et en Mediterranee occidentale (Prosperi et a/., 1991 (Prosperi et a/., 1991) ; M. ciliaris est aussi considere comme frequent en Algerie (39.6%) (Abdelguerfi, 1978 ;Abdelguerfi et a/., 1988aAbdelguerfi et a/., et 1988b. Au Maroc, Bounejmate ( 1992) et Bounejmate et a/.…”
Section: Abstract-m Ci/iaris and M Intertexta Taxons Are Relativelmentioning
confidence: 99%
“…The results of these networks have been scientifically very fruitful, resulting in large and well-organised genetic resource collections, such as those undertaken in Libya (Gintzburger and Blesing 1979), Sardinia (Piano et al 1982), and Morocco (Bounejmate et al 1992). The networks continue in operation with ongoing collaboration, an example of which is the current collaboration in the domestication of tedera (Bituminaria bituminosa var.…”
Section: Networking and Advocacymentioning
confidence: 99%